Scavenger-free and self-powered photocathodic sensing system for aqueous hydrogen peroxide monitoring by CuO/ZnO nanostructure - Hao, Wu; Hoi, Ying Ching; Tsang, Daniel C.W; Huang, Nay Ming; Xie, Zhirun; Lim, Hong Ngee; Yong, Sik Ok; Ng, Yun Hau (Elsevier, 2020)
A scavenger-free and self-powered photoelectrochemical sensor is developed to rapidly detect hydrogen peroxide (H2O2) in the aqueous phase. The resulting CuO/ZnO photocathode composite exhibits two-times higher photocurrent density than the bare CuO under simulated sunlight irradiation, attributed to the formed CuO/ZnO heterojunction with well-aligned band energy levels which promotes the interfacial charge separation of photogenerated electron-hole pairs. Herein, the resulting photocathode composite is assembled as a photoelectrochemical hydrogen peroxide sensor, which shows an instant response within 0.1 s and an approximately 3-fold increase in photocurrent density upon adding 30 mM of H2O2 into the electrolyte. The results further demonstrate that the effect of H2O2 on photocurrent response is concentration-dependent over the wide linear ranges of 0.2–1.0 mM and 1.0–8.0 mM with strong correlations (R2) of 0.992 and 0.986, respectively. The proposed CuO/ZnO photocathode composite can guide the design of efficient hybrid photoelectrodes for solar energy conversion applications.